Molecular Pathways of Ashwagandha in Stress Regulation: An Integrative Study of HPA Axis and Ayurvedic Rasayana Concept - Dr. Sukhdevsinh Kamariya,; Dr. Amit J. Upasani,; Dr. Yogesh B. Mandle, (The Bioscan, 2026)
The Ashwagandha (Withania somnifera), which is regarded to be the best Rasayana in Ayurveda is rapidly being used in contemporary biomedical research on its multifunctional adaptogen and neuroendocrine modulatory properties. The paper examines the molecular crosstalk of the phytoconstituents of Ashwagandha, especially the withanolides, with the hypothalamic-pituitary-adrenal (HPA) axis, and how it coordinates the stress resilience mechanism by modulating the glucocorticoid receptors, neurostimulatory, and oxidative homeostasis. Combining Ayurvedic with molecular pharmacology, this paper will conceptualize Ashwagandha as a molecular Rasayana -balance of overall vitality in the system in addition to resetting stress responses on the neuro endocrine side. By refraining to reduce Ayurvedic wisdom to the neurobiological frameworks of the day, the research paper outlines a holistic route of stress management that goes beyond the reductionist theories. It is synthesized that Ashwagandha may serve as a translational model of integrative medicine of molecular specificity and traditional wisdom to change the psychoneuroendocrine homeostasis.